2020
DOI: 10.1038/s41396-020-0713-4
|View full text |Cite
|
Sign up to set email alerts
|

A widely distributed hydrogenase oxidises atmospheric H2 during bacterial growth

Abstract: Diverse aerobic bacteria persist by consuming atmospheric hydrogen (H2) using group 1h [NiFe]-hydrogenases. However, other hydrogenase classes are also distributed in aerobes, including the group 2a [NiFe]-hydrogenase. Based on studies focused on Cyanobacteria, the reported physiological role of the group 2a [NiFe]-hydrogenase is to recycle H2 produced by nitrogenase. However, given this hydrogenase is also present in various heterotrophs and lithoautotrophs lacking nitrogenases, it may play a wider role in ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 64 publications
7
35
0
Order By: Relevance
“…In energy-deprived desert soils, a key role of this hydrogenase is likely to recycle H 2 endogenously produced by the energetically demanding nitrogenase reaction, as previously reported for other Nostoc strains (71,72). However, given recent discoveries regarding the physiological role of group 2a [NiFe]-hydrogenase (51), it is also plausible that this hydrogenase enables these bacteria to conserve energy by scavenging exogenous H 2 . Together, these genomic inferences provide considerable support for the continual energy-harvesting hypothesis by uncovering flexibility in energy conservation and carbon acquisition pathways, including hydrogenases associated with the most abundant chemoheterotrophic and photoautotrophic taxa.…”
Section: Figmentioning
confidence: 61%
See 2 more Smart Citations
“…In energy-deprived desert soils, a key role of this hydrogenase is likely to recycle H 2 endogenously produced by the energetically demanding nitrogenase reaction, as previously reported for other Nostoc strains (71,72). However, given recent discoveries regarding the physiological role of group 2a [NiFe]-hydrogenase (51), it is also plausible that this hydrogenase enables these bacteria to conserve energy by scavenging exogenous H 2 . Together, these genomic inferences provide considerable support for the continual energy-harvesting hypothesis by uncovering flexibility in energy conservation and carbon acquisition pathways, including hydrogenases associated with the most abundant chemoheterotrophic and photoautotrophic taxa.…”
Section: Figmentioning
confidence: 61%
“…These findings are supported by pure culture studies that show high-affinity hydrogenases are most expressed in carbon-limited cells (43)(44)(45)(46)(47) and, when knocked out, result in decreased long-term survival (48)(49)(50). Diverse bacteria can also support mixotrophic growth using atmospheric H 2 (51)(52)(53)(54). Overall, atmospheric H 2 is a highly dependable substrate for bacteria in oligotrophic environments given that it is ubiquitous in the lower atmosphere (mixing ratio, 0.53 ppmv), has a low activation energy, and yields a large amount of free energy when oxidized (55)(56)(57)(58).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Four distinct bacterial phyla containing a number of acidophiles (Actinobacteriota, Acidobacteriota, Chloroflexota, and Verrucomicrobiota) have been experimentally shown to utilize atmospheric H 2 by the [NiFe] group 2a hydrogenase (Islam et al, 2020). To date, autotrophic growth by dissimilatory H 2 oxidation has been reported only for several acidophiles.…”
Section: Introductionmentioning
confidence: 99%
“…ferrooxidans ATCC 23270 T genome has been shown to encode four different types of [NiFe] hydrogenases: (i) membrane-bound respiratory [NiFe] group 1 hydrogenase, (ii) cyanobacterial uptake and cytoplasmic [NiFe] group 2 hydrogenase, (iii) bidirectional hetero-multimeric cytoplasmic [NiFe] group 3 hydrogenase, (iv) H 2 -evolving, energy-conserving, membrane-associated [NiFe] group 4 hydrogenase (Valdés et al, 2008). Even though H 2 as an electron donor has several advantages for acidophiles compared to other inorganic substrates, including avoiding generating or consuming acidity and Fe 3+ precipitation, few physiological studies have been reported (Fischer et al, 1996;Ohmura et al, 2002;Islam et al, 2020), and no detailed information on H 2 uptake and metabolic pathways in acidophilic mesophiles is available. Recently, the energy metabolism pathways for autotrophic growth on H 2 in thermoacidophilic methanotrophs of the genus Methylacidiphilum and Methylacidimicrobium (both Verrucomicrobia) from extremely acidic geothermal systems have been proposed (Carere et al, 2017;Mohammadi et al, 2019;Schmitz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%